Tht First Company of the National Economy: Anatolian National Crops Ottoman Joint Stock Company - Saya, Mehmet; Alkis, Muhammed Cihad (Journal of Applied And Theoretical Social Sciences, 2021)
The political liberalism that emerged after Second Constitutional Monarchy also reflected on the economy of the period and caused the non-Muslims to increase their activities in the economy. At first, this new situation of non-Muslims was not a problem but Tripoli’s loss and land loss in the Balkans caused strengthened nationalist discourses and with the outbreak of the First World War, it also strengthened the idea of ​​national economy, which was voiced before, and led this idea to find a better ground. The Committee of Union and Progress, which was in power during the war, intervened in the economy and encouraged the establishment of national companies for the subsistence of the country, while directing the Muslim-Turkish element to a favoured entrepreneurship and ignoring the speculative gains in order to create a domestic and national bourgeoisie. Anatolian National Crops Ottoman Joint Stock Company was established in 1915 as the first company that the national economic policy found an area of application. Anatolian National Crops Ottoman Joint Stock Company is important in terms of being the first company and testing the success of national economic policies. The aim of this study is to examine Anatolian National Crops Ottoman Joint Stock Company, which is the first company of the national economic policy, through the establishment regulations, reports on the activities of the company for two years, document and other sources which can be accessed from the archives of the National Library of Turkey, The Turkish History Foundation and Directorate of State Archives.